One-Step Process for Environment-Friendly Preparation of Agar Oligosaccharides From Gracilaria lemaneiformis by the Action of Flammeovirga sp. OC4 - Chen, Xinglin; Li, Li; Chan, Zhuhua; Zeng, Runying; Lin, Mengshi; Lin, Hetong (Frontiers in Microbiology, 2019)
Oligosaccharides extracted from agar Gracilaria lemaneiformis (G. lemaneiformis) have stronger physiological activities and higher value than agar itself, but the pollution caused by extraction process greatly restricts the sustainable use of agar. In this study, four bacterial strains with high ability of degrading G. lemaneiformis were isolated from seawater by in situ enrichment in the deep sea. Among them, Flammeovirga sp. OC4, identified by morphological observation and its 16S rRNA sequencing (98.07% similarity to type strain JL-4 of Flammeovirga aprica), was selected. The optimum temperature and pH of crude enzyme produced by Flammeovirga sp. OC4 were 50 °C and 8, respectively. More than 60% of the maximum enzyme activity remained after storage at pH 5.0 - 10.0 for 60 min. Both Mn2+ and Ba2+ could enhance the enzyme activity. An ‘one-step process’ for preparation of oligosaccharides from G. lemaneiformis was established using Flammeovirga sp. OC4. After optimization of Plackett-Burman (PB) design and response surface methodology (RSM), the yield of oligosaccharides was increased by 36.1% from 2.71 to 3.09 g L-1 in a 250 mL fermenter with optimized parameters: 30 g L-1 G. lemaneiformis powder, 4.84 g L-1 (NH4)2SO4, 44.8 mL working medium volume at 36.7 °C, and a shaking speed of 200×g for 42 h. The extracted oligosaccharides were identified by thin layer chromatography (TLC) and ion chromatography, which consisted of neoagarobiose, agarotriose, neoagarotetraose, agaropentaose, and neoagarohexaose. These results provided an alternative approach for environment-friendly and sustainable utilization of algae.